El Método ABN como articulador efectivo de aprendizajes matemáticos en la infancia: experiencias en profesores y profesoras de ciclo inicial en Chile - CARLOS PEREZ; Ivonne González; Gamal Cerda; Guido Benvenuto (LED Edizioni Universitarie, 2018)
Results are presented abut a professional development workshop based on the ABN Method for learning mathematics (N = 27), conducted in Talca, Chile, for Pre-K and Primary in-service teachers (children from 4 to 7 years of age in charge). The workshop is aimed at nursery school teachers and first grade teachers. The ABN Method is based on the significant learning of the decimal number system and on the complete domain of operations and their properties, which are learned and assimilated at the same time by children from the early stages of teaching. The results of the study show that the participation of teachers in the workshop generated significant changes in a set of teachers' beliefs, as well as a favorable change in the perception regarding the mathematical ability of their students. Finally, teachers report a greater conceptual clarity regarding the sequencing of contents and the purpose of the mathematical activities they perform in the classroom. The results and implications of this workshop are discussed.